Vet4Cat: cat health and illness symptom checker using rule based / Siti Nurfateha Abd Jalil - Abd Jalil, Siti Nurfateha (Faculty of Computer and Mathematical Sciences, 2019)
Keeping cats is a growing trend in Malaysia. Learning more about cat diseases and their treatment is one of the best investments a cat owner can do for the pet’s health and comfort. However, one of the main reason that the cat falls sick is because of the poor awareness among the cat owners about the health requirements of their cat. This includes lack of knowledge and understanding about the cat health, expensive cost of the vet visits and time constraints to bring the cat to the clinic. In order to reduce these problems, a mobile application on cat illness symptom checker is developed to assist the owner to determine the possible diseases and provide alternative treatments based on the information provided by the expert. Thus, the objective of this application is to develop a mobile application that provides information as well as suggesting suitable treatment on how to treat a sick cat, and to evaluate the accuracy of the cat illness symptom checker using rule based expert system. The methodology use in this project is Waterfall model while the technique applied in this project is rule based expert system. The outcome of this mobile application is that user will be able to identify the best treatment for every disease that may suffered by their cat. Furthermore, other features included in this mobile application is ability for the cat owner to locate the nearest veterinary clinic based on their current location and a reminder function where cat owner can use to add reminders for their cat such as appointment or vaccination. For future works, other disease problems can be added into the application as for now it only focuses on the most common cat health issues in Malaysia.